An investigation on the effects of lime and/or phosphorus fertilizer applications on soil organic matter preservation : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Soil Science at Massey University, Manawatu, New Zealand - Li, Yang (Massey University, 2021)
The poor understanding of the mechanisms through which soil organic matter (OM) is lost with ongoing land-use intensification hampers the development of food security and climate-smart agricultural management practices. The overall objective of this thesis was to investigate the effect of lime and/or phosphorus (P) amendment on OM preservation in a volcanic soil classified as an Andosol – the mineral soil group with the largest organic carbon (OC) content worldwide and characterised by its abundance in aluminium (Al)-OM complexes (e.g., Al³⁺-OM and allophane-OM complexes). Special attention was paid to the response of OM stabilisation and mineralisation with depth to these amendments. Firstly, we hypothesised that (i) lime and P application has an impact on OM stabilisation through different mechanisms, and (ii) their effect is synergic. To have a direct understanding of the effect of lime and/or P application on OM preservation in the Andosol under study, we conducted a batch of water extractions. We extracted the bulk soil and its heavy fraction (>1.6 g/cm3, indicative of the presence of OM-mineral associations) with added lime and/or P to reveal the individual and combined influence of lime and P amendments on water-extractable OM (WEOM), which has been deemed to be an indicator of OM destabilisation. The results obtained from quantitative analyses of WEOM showed that adding lime and/or P significantly increased the WEOM, along with a decrease in its carbon (C)/nitrogen (N) ratio (C/N) and an increase in its aromaticity. The chemical composition of WEOM measured by pyrolysis-gas chromatography/mass spectrometry suggested that lime and P addition (at high application rate) caused an enrichment in WEOM in the poly- and monophenolic, and nitrogenised fraction, as well as in plant-derived polysaccharides. If we consider the effect on the heavy fraction, the increase in WEOM was still consistent with that observed in the bulk soil when lime was applied, but the response to P addition alone was smaller. These findings indicate that lime and P amendment to soils rich in Al-OM complexes cause destabilisation of OM, but through different mechanisms. Phosphate was found to mainly impact Al³⁺-OM complexes (partly present in the removed free particulate OM) by outcompeting organic ligands for Al³⁺, whereas alkalisation was able to disrupt both the Al³⁺-OM and allophane-OM complexes, and the stability of aggregates. These could be hastened by combined lime and P addition, as made evident by the larger impact of combined lime and P amendments than that of either P or lime addition alone (Chapter 3). After confirming the occurrence of OM destabilisation in the Andosol upon lime and/or P application, we hypothesised that the response of OM preservation (OM stabilisation and mineralisation) to these amendments varies with soil depth. We conducted a 6-month incubation experiment to have an in-depth understanding of the influence of these amendments on OM preservation in soil at different depths. A topsoil (rich in Al³⁺-OM complexes) and a subsoil (with a greater abundance of allophane) of an alu-andic Andosol was incubated with/without inorganic amendments (either lime, phosphate or lime+phosphate) in the presence or absence of an organic amendment (¹³C- and ¹⁵N- labelled barley, Hordeum vulgare L.). By conventional chemical analyses of the bulk soil, we showed an increase in WEOM in both topsoil and subsoil samples that received amendments, particularly of lime (with/without P). However, through a nano-scale secondary ion mass spectrometry analysis of OM-mineral associations in soil microaggregates, we noted that lime amendments decreased OM coverage (particularly plant-derived OM) on the mineral surface in topsoil, but increased it in subsoil (with enhanced coverage of plant-derived OM). These suggested that at these two soil depths with different biogeochemistry, lime addition resulted in OM destabilisation through different mechanisms associated with (i) the displacement of OM from inorganic surfaces in microaggregates in the topsoil, and (ii) the release of OM previously protected within macroaggregates in the subsoil. The total cumulative carbon dioxide (CO₂) emissions and stable C isotopic signature (δ¹³C) of CO₂ showed that lime amendments caused an increase in OM decomposition in the subsoil from both inherited OM (priming) and OM newly formed from barley litter decomposition, but not in topsoil. The increase in OM mineralisation observed in the subsoil (a harsher environment for microbes, with limited bioavailable OM) is consistent with the fact that more favourable conditions were generated by the lime and P addition, which caused an increase in WEOM (Chapter 4). To further understand the distinct responses in OM mineralisation with depth to lime and/or P amendments, we investigated soil bacterial and fungal community composition and their functional profile through high-throughput sequencing analysis. A shift in bacterial and fungal community composition and their functional composition was found in the limed topsoil but not in the limed subsoil. Through structural equation modelling analysis, it was found that in the topsoil, microbial properties, particularly the fungal community composition and functional profile, had a significant relationship with OM mineralisation (with a relatively greater positive or negative coefficient value than other factors). However, in the subsoil, OM mineralisation was only significantly correlated with labile OM in the subsoil. These findings suggested that in the Andosol, the key regulator controlling the response of OM mineralisation to lime and/or phosphate addition shifted with depth from microbial composition and functionality to bioavailable C substrate (Chapter 5). All the results obtained in this thesis contribute to providing a mechanistic understanding of the effect of lime and/or P amendments on OM stabilisation and mineralisation, and have implications for designing climate-smart agricultural management practices of soils with abundant Al-OM complexes.
Keywords: Andosols; Humus; Liming of soils; Phosphatic fertilizers; New Zealand; 300204 Agricultural management of nutrients